Transfusion of blood components containing ABO‐incompatible plasma does not lead to higher mortality in civilian trauma patients. Issue 11 (9th September 2020) - Seheult, Jansen N.; Dunbar, Nancy M.; Hess, John R.; Tuott, Erin E.; Bahmanyar, Mohammad; Campbell, Jessica; Fontaine, Magali; Khan, Jenna; Ko, Ara; Mi, Jian; Murphy, Michael F.; Nykoluk, Tara; et al.
Abstract: Background: This study investigated the effect on mortality of transfusing ABO‐incompatible plasma from all sources during trauma resuscitation. Methods: Demographic, transfusion, and survival data were retrospectively extracted on civilian trauma patients. Patients were divided by receipt of any quantity of ABO‐incompatible plasma from any blood product (incompatible group) or receipt of solely ABO‐compatible plasma (compatible group). The primary outcome was 30‐day mortality, while other outcomes included 6‐ and 24‐hour mortality. Mixed‐effects logistic regression was used to model the effect of various predictor variables, including receipt of incompatible plasma, on mortality outcomes. Results: Nine hospitals contributed data on a total of 2618 trauma patients. There were 1282 patients in the incompatible group and 1336 patients in the compatible group. In both the unadjusted and adjusted models, the 6‐hour, 24‐hour, and 30‐day mortality rates were not significantly different between these groups. The patients in the incompatible group were then divided into high volume (>342 mL) and low volume (≤342 mL) incompatible plasma recipients. In the adjusted model, the high‐volume group had higher 24‐hour mortality when the Trauma Injury Severity Score survival prediction was >50%. Mortality at 6 hours and 30 days was not higher in this model. The low‐volume group did not have increased mortality at any of the time points in this adjusted model. Conclusion: The transfusion of incompatible plasma in civilian trauma resuscitation does not lead to higher 30‐day mortality. The finding of higher mortality in a select group of recipients in the secondary analysis warrants further study.